2011
DOI: 10.1080/15397734.2011.524574
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Laminated Cantilever Composite Beams by Model Order Reduction Techniques

Abstract: In this study, a laminated cantilever composite beam is studied in frequency domain by using some popular model order reduction techniques. In the analyses, component mode synthesis (CMS) and quasi-static mode synthesis (QSM1, QSM2) methods are applied to semi-discrete finite element equations to obtain reduced order models for structural analyses. The performance of the model order reduction methods is compared. In addition, fiber orientation, stacking sequence, ply thickness, and its location effects on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…In this section first order shear deformation theory, namely Timoshenko's beam theory, is to be used in the formulation to account for the shear deformation and rotatory inertia effects (Cunedioğlu 2011;Kim and Jeon 2013;Ghannadias and Mofid 2014). In the theory, which offers the simple and acceptable solutions, the shear correction factor, k-factor, appears as a coefficient in the expression for the transverse shear stress resultant, and considers the shear deformation effects with a good approximation as a result of non-uniform distribution of the shear stresses over the cross-section of the beam.…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section first order shear deformation theory, namely Timoshenko's beam theory, is to be used in the formulation to account for the shear deformation and rotatory inertia effects (Cunedioğlu 2011;Kim and Jeon 2013;Ghannadias and Mofid 2014). In the theory, which offers the simple and acceptable solutions, the shear correction factor, k-factor, appears as a coefficient in the expression for the transverse shear stress resultant, and considers the shear deformation effects with a good approximation as a result of non-uniform distribution of the shear stresses over the cross-section of the beam.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…That is, no study has been found on the analysis of composite helical springs subjected to an initial axial force except for Kacar and Yildirim's study (2011). In the present work which is handled first time, two important phenomena namely the buckling and vibrational analyses of the most commonly used helical compression springs subjected to an initial axial force are studied by extending Yildirim's and Kacar's studies (2009a, 2009b, 2011Yildirim 2012) to unidirectional composite springs.…”
mentioning
confidence: 99%
“…It can be calculated by using the relation (12) For interval systems, 1] is calculated after converting the interval coefficients G(s) and R(s) into the fixed coefficients by taking their means. Thus the gain correction factor is: The step responses of the original system, the second order model obtained by the proposed method and the model given Step Response Step Response Time(s) Step Response This increases significantly the usefulness of the method and give good approximation in steady-state response matching.…”
Section: B Determination Oj Reduced Numeratormentioning
confidence: 99%
“…Recently the analysis, stability and transients of interval systems attracted the attention of many researchers [6][7] [8]. But only few methods are available in literature for order reduction of interval systems [9] [10] [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, there are some numerical studies performed making use of the finite element method (FEM) and/or Ritz vectors-eigenvectors to compute the behavior of structural members (Karasin and Gulkan, 2007;Zhou and Zheng, 2008;Cunedioglu, 2011;Jung et al, 2011;Özütok and Madenci, 2013;Mazurkiewicz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%